The adequacy of micronutrient concentrations in manufactured complementary foods from low-income countries - Michelle Gibbs (2018)
Iron, zinc, and calcium in complementary foods (CFs) are defined as problem micronutrients by the World Health Organization (WHO), as their concentrations in CFs fall below the calculated requirements for breast-fed infants of micronutrients obtained from CFs. Consequently, manufacturers often fortify plant-based CFs with these three micronutrients. We have analyzed concentrations of iron, zinc, calcium, and phytic acid (as hexa- and penta-inositol phosphates) in 57 cereal-based CFs pu rchased in five countries each in Africa and Asia. Molar ratios of phytate:iron, phytate:zinc, and phytate:calcium were also calculated. Intakes of iron, zinc, and calcium from these CFs were then calculated assuming breast-fed infants aged 9-11 months consume the recommended daily ration size of CF (40. g/d; dry weight), and compared with WHO estimated needs from CFs. Even though manufacturers claimed to fortify 84% (48/57) of the CFs, 79%, 10% and 32% had molar ratios for phytate:iron, phytate:zinc, and phytate:calcium, respectively, above desirable levels. Despite fortification, only ∼4% of the CFs met the WHO estimated needs for breast-fed infants aged 9-11 months for iron, 2% for zinc, and ∼4% for calcium. Appropriate fortification of cereal-based CFs is necessary to ensure they meet WHO estimated needs for iron, zinc, and calcium for breast-fed infants. © 2011.